2023
DOI: 10.1111/josh.13296
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Perceptions of COVID‐19‐related Emotional Impact on Mental Health Among Early Adolescents in Appalachia

Abstract: Background Young people who experience higher levels of social support from their schools and families have been shown to be less likely to develop symptoms of negative mental health outcomes such as depression and anxiety.1–4 This raises questions concerning how young people's stress and psychological changes due to the COVID‐19 pandemic as well as social support during this time have affected their overall mental health. The aim of this study was to assess the association between sources of parental‐ and sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For adolescents and young people, the absence of social support such as school and parental social support, may increase the possibility for mental health problems 60 , 61 . Adolescents and young people experience significant physical and emotional changes, and often navigate complex social dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For adolescents and young people, the absence of social support such as school and parental social support, may increase the possibility for mental health problems 60 , 61 . Adolescents and young people experience significant physical and emotional changes, and often navigate complex social dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The role of social support in the lives of young people during the Covid-19 pandemic has been seen to be crucial. Studies have shown that young people who have received support from family and school, have been less predisposed to exhibit negative symptoms or mental health deterioration, although they have experienced the challenges and changes caused by Covid 19 (Layman et al, 2023). Social support includes care and attention from parents, caregivers, actors within the school, as well as peers for young people when they are bored, to do things with them and to talk, especially in a specific challenging area (Layman et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that young people who have received support from family and school, have been less predisposed to exhibit negative symptoms or mental health deterioration, although they have experienced the challenges and changes caused by Covid 19 (Layman et al, 2023). Social support includes care and attention from parents, caregivers, actors within the school, as well as peers for young people when they are bored, to do things with them and to talk, especially in a specific challenging area (Layman et al, 2023). With the interruption of learning in schools, the challenges of adapting to online learning and the limitation of social interactions, young people have shown a higher level of psychological distress (Arënliu & Bërxulli, 2020), and on the other hand, they have also reported difficulties in career planning (Jemini-Gashi & Kadriu, 2022).…”
Section: Introductionmentioning
confidence: 99%